Heterogeneous Bank Lending Responses to Monetary Policy : New Evidence from a Real-time Identification - Bluedorn, John (IMF Working Papers; Working Paper ;, 2013)
We present new evidence on how heterogeneity in banks interacts with monetary policy changes to impact bank lending. Using an exogenous policy measure identified from narratives on FOMC intentions and real-time economic forecasts, we find much greater heterogeneity in U.S. bank lending responses than that found in previous research based on realized federal funds rate changes. Our findings suggest that studies using realized monetary policy changes confound the monetary policy's effects with those of changes in expected macrofundamentals. We also extend Romer and Romer (2004)'s identification scheme, and expand the time and balance sheet coverage of the U.S. banking sample.